Venovenous extracorporeal membrane oxygenation support in patients with COVID-19 respiratory failure: A multicenter studyCentral MessagePerspective - Navin G. Vigneshwar, MD, MPH; Muhammad F. Masood, MD; Ivana Vasic, BS; Martin Krause, MD; Karsten Bartels, MD, PHD; Mark T. Lucas, MPS; Michael Bronsert, PhD; Craig H. Selzman, MD; Shaun Thompson, MD; Jessica Y. Rove, MD; Thomas B. Reece, MD; Joseph C. Cleveland, MD; et al. (JTCVS Open, 2022)
Objective: The COVID-19 pandemic presents a high mortality rate amongst patients who develop severe acute respiratory distress syndrome (ARDS). The purpose of this study was to evaluate the outcomes of venovenous extracorporeal membrane oxygenation (VV-ECMO) in COVID–19-related ARDS and identify the patients who benefit the most from this procedure. Methods: Adult patients with COVID-19 and severe ARDS requiring VV-ECMO support at 4 academic institutions between March and October 2020 were included. Data were collected through retrospective chart reviews. Bivariate and multivariable analyses were performed with the primary outcome of in-hospital mortality. Results: Fifty-one consecutive patients underwent VV-ECMO with a mean age of 50.4 years; 64.7% were men. Survival to hospital discharge was 62.8%. Median intensive care unit and hospitalization duration were 27.4 days (interquartile range [IQR], 17-37 days) and 34.5 days (IQR, 23-43 days), respectively. Survivors and nonsurvivors had a median ECMO cannulation time of 11 days (IQR, 8-18) and 17 days (IQR, 12-25 days). The average postdecannulation length of stay was 17.5 days (IQR, 12.4-25 days) for survivors and 0 days for nonsurvivors (IQR, 0-6 days). Only 1 nonsurvivor was able to be decannulated. Clinical characteristics associated with mortality between nonsurviors and survivors included increasing age (P = .0048), hemorrhagic stroke (P = .0014), and postoperative dialysis (P = .0013) were associated with mortality in a bivariate model and retained statistical significance in a multivariable model. Conclusions: This multicenter study confirms the effectiveness of VV-ECMO in selected critically ill patients with COVID–19-related severe ARDS. The survival of these patients is comparable to non-COVID–19-related ARDS.